Stability of a second‐order method for phase change in porous media flow. Issue 1 (17th December 2018) - Alvarez, Mario; Gomez‐Vargas, Bryan; Ruiz Baier, Ricardo; Woodfield, James
Abstract: We analyse the stability of a second‐order finite element scheme for the primal formulation of a Brinkman‐Boussinesq model where the solidification process influences the drag and the viscosity. The problem is written in terms of velocity, temperature, and pressure, and we produce numerical approximations to the flow observed in heated cavities and near ice sheets.